Kepastian Hukum Pensertipikatan Tanah Secara Massal Melalui Proyek Operasi Nasional Agraria - Dinda Suryo Febyanti (Jurnal Ilmu Kenotariatan, 2022)
Regarding the issue of land registration, the government is carrying out the operationalization of national agrarian (prona) land certification on a mass scale and is strategic land. The land registration program through Prona is a land registration program intended for low-income households. In this case, prona process the certificate and cultivation in a very short time, but must not forget the high level of care and accuracy in submitting it. Because if there is a mistake or negligence it will cause the goal to be achieved, namely certainty regarding this matter, to be canceled. This writing uses a normative juridical type, with a statutory approach and a conceptual approach. The results of the discussion regarding understanding of this matter, which failed, especially regarding aspects of registration administration and that. The aims and functions of this project are Prona 1) carrying out mass prona, land word programs throughout Indonesia, 2) holistically resolving strategic land disputes. Conclusion Legal certainty regarding mass land certification through the national agrarian operations project, the author can conclude that to ensure legal certainty the Government is holding land registration throughout the territory of Indonesia according to the provisions regulated by Government Regulations. . As well as regulating the fees related to registration as referred to in paragraph (1) above, with the provision that people who cannot afford it are exempted from paying these fees. So that it has fulfilled the legal certainty that applies in positive law in Indonesia. KEYWORDS: Legal Certainty, Land Certificates, PRONA